FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KELUHAN LOW BACK PAIN (LBP) PADA PEKERJA KONSTRUKSI PROYEK PEMBANGUNAN 6 RUAS TOL DALAM KOTA JAKARTA SEKSI 1A - Zefanya Geraldine Ruthin (2021)
Low Back Pain (LBP) can be caused by several factors, such as individual, environment, and occupational factors. Some types of work that are high risk of causing LBP complaints to construction workers are lifting and moving materials, scaffolding installation, reinforcement, housekeeping, and others. The purpose of this study was to determine the factors associated with LBP complaints in construction workers of Project 6 Inner-City Toll Road Segment in Jakarta Section 1A. The research method is quantitative analytics with Cross Sectional approach. The samples in this study were 100 construction workers of Project 6 Inner-City Toll Road Segment in Jakarta Section 1A. The results showed that about 62% of construction workers in this project had LBP complaints. Most of the respondents in this study were young, were light smokers, had a normal BMI, long working period, normal working hours, low workload and performed MMH category 2 (OWAS). Based on the results of statistical analysis, it can be concluded that there is a relationship between age, BMI, smoking behavior, work duration, workload, MMH with LBP complaints.